Chinese consumer preference for processed food quality attributes and the impact of trust in information sources. Issue 3 (29th July 2021) - Wang, Erpeng; Gao, Zhifeng; Chen, Xuqi
Abstract : Purpose: The purpose of this paper is to determine important attributes of processed food, consumers' trust in different information resources, and the impact of trust, demographic and behavior variables on the preference of processed food attributes among Chinese consumers. Design/methodology/approach: Data of 1, 267 participants were collected from four cities in China. A five-point Likert scale was used to measure consumer preference for 12 juice attributes. Consumer trust in nine sources of information on product quality was measured. Cluster analysis was used to segment consumers into groups based on their preference for juice attributes and trust in information sources, respectively. A multinomial logistic model was used to determine the impact of trust, demographic and behavior variables on the preference of juice attributes. Findings: Consumers rate manufacture date, taste and food safety labels as the most important attributes of fruit juice products. Among different information sources, consumers place more trust in private information sources and traditional media. The low trust in different information sources impedes consumer preference for processed food quality attributes. Originality/value: This research is among the few that examine consumer preference for processed food, such as juice. It identifies four distinct preference groups and trust groups, respectively, based on consumer preference for juice attributes and trust in different information sources. This paper provides important information for processed food companies and policymakers to effectively enact marketing strategies in China.